Social and non-social risk-taking in adolescence - Weike Wang; Kylie Evans; Susanne Schweizer (Scientific Reports)
Abstract The Social Risk Hypothesis of Depression proposes that individuals who perceive themselves as low in value to their social groups are at risk of developing depression. Behaviourally, lower self-perceived social value is proposed to reduce individuals’ propensity to take social risks to avoid further lowering their social worth. This is in contrast with adolescent-typical behaviour, which is characterised by heightened risk-taking in social contexts. The current study aimed to investigate how low self-perceived social value influences risk-taking in social compared to non-social contexts during adolescence. 114 adolescents (aged 12–23 years) completed the Balloon Analogue Risk Task (BART) in individual and social contexts. The results showed that adolescents took more risks in social compared to individual contexts. Risk-taking across social and individual contexts also varied as a function of self-perceived social value. In older—but not younger—youth, lower self-perceived social value was associated with greater risk-taking in social compared to individual contexts. These findings suggest that self-perceived social value differentially influences social risk-taking across adolescence. In later youth, the heightened social risk-taking observed in individuals with low self-perceived social value aligns with developmental theories suggesting that risk-taking at this age serves to increase social rank and avoid social exclusion by peers.